Comparison of Phenylephrine and Ephedrine in Managing Spinal-Induced Hypotension in Lower Segment Caesarean Section (LSCS): Phenylephrine and Ephedrine in Managing Spinal-Induced Hypotension in LSCS - Shah, Madiha; Janjua, Sarfaraz Khan; Javaid, Urba; Shameem, Asad; Anjum, Waqas; Ali, Wajid; Rafique, Zohaib (Pakistan Journal of Health Sciences, 2026)
Spinal-induced hypotension is a frequent complication of spinal anesthesia during lower-segment caesarean section and may adversely affect maternal comfort and uteroplacental perfusion. Phenylephrine and ephedrine are commonly used vasopressors, but they differ in their cardiovascular effects. Objectives: To compare systolic blood pressure stabilization, heart rate changes, vasopressor dose requirements, and maternal outcomes between phenylephrine and ephedrine. Methods: This prospective observational comparative cohort study was conducted at the Department of Anesthesiology, Hazrat Bari Imam Sarkar Medical and Dental College, and Hazrat Bari Imam Sarkar Teaching Hospital, Islamabad. Two hundred parturient who developed spinal-induced hypotension were enrolled (100 received phenylephrine and 100 ephedrine). Hemodynamic parameters were recorded at baseline and at 3 and 6 minutes after vasopressor administration. Data were analyzed using an independent-samples t-test, a Mann–Whitney U test, and a Chi-square test. Results: Phenylephrine maintained significantly higher systolic blood pressure at 3 minutes (p=0.008). Ephedrine was associated with significantly higher pulse and heart rate (p=0.003 and p=0.004). Bradycardia was more frequent with phenylephrine (p=0.001), while tachycardia and higher repeat-dose requirements were more common with ephedrine (p=0.025 and p=0.017). Duration of hypotension was significantly shorter with phenylephrine (p=0.003). Conclusions: Both vasopressors effectively managed spinal-induced hypotension; however, phenylephrine provided more stable systolic control and faster recovery, whereas ephedrine caused greater heart rate variability.